ANALISIS KEBUTUHAN PENGEMBANGAN MODUL AJAR BERBASIS PBL PADA MATERI PERUBAHAN DAN PELESTARIAN LINGKUNGAN HIDUP UNTUK PESERTA DIDIK FASE E SMA - Putri, Ainil; Ristiono (Universitas Cokroaminoto Palopo, 2024)
Education is an important thing in a nation. Education is one of the determinants of the nation's progress. Indonesia strives to improve the quality of education in Indonesia with an independent curriculum. Freedom of learning is a policy of the Ministry of Education and Culture of the Republic of Indonesia. The Independent Curriculum is implemented with the aim of training students' independence in thinking. Schools need to adapt to the policies that have been regulated in this curriculum, especially in the preparation of learning tools that are in accordance with the independent curriculum. Teaching tools in the independent curriculum are known as teaching modules. Teaching modules are a form of teaching tool used by educators to carry out learning with the aim of achieving Pancasila student profiles and Learning Outcomes. Guided by the flow of existing learning objectives, in the material of environmental change and preservation, students are required to be able to think critically and creatively. Therefore, one of the models that leads students to think critically and creatively in the learning process is the problem-based learning model. This study aims to analyze the needs of students and teachers for the development of PBL-based teaching modules on environmental change and conservation materials for students in class X phase E of high school. The research method used is a descriptive method. The research data used was the result of teacher interviews and student questionnaires in West Pasaman Regency. The results of the study show that the development of PBL-based teaching modules on environmental change and conservation materials for students in class X phase E of high school is urgently needed.